Mining Paradox, Social Capital, and Education: A Dynamic Econometric Approach to Sustainable Communal Economic Development - Habel Taime; Siska Sroyer (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Papua Province is home to one of the largest mining operations in the world, yet the indigenous Kamoro and Amugme peoples of Mimika Regency remain trapped in persistent poverty and limited access to education and healthcare. This paradox reflects a broader resource curse dynamic in which abundant natural resources fail to translate into meaningful welfare improvements for local communities. This study aims to analyze the long-term effects of mining dependency, education, and social capital on the welfare of indigenous peoples in Mimika Regency, and to propose a sustainable communal economic model grounded in local wisdom as an alternative development pathway. Secondary panel data covering the period from 2000 to 2025 were analyzed using the System Generalized Method of Moments to address endogeneity and dynamic panel data issues. The results show that mining dependency significantly reduces indigenous welfare, while education and social capital both contribute positively and significantly to welfare improvement. Prior welfare conditions also positively influence current welfare, confirming path dependency in development outcomes. These findings suggest that sustainable welfare improvement in Papua requires a deliberate shift away from extractive dependency toward community-centered policies that strengthen customary institutions, expand educational access, and integrate indigenous local wisdom into regional development planning.